1997
DOI: 10.1063/1.119701
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of regular arrays of antidots in YBa2Cu3O7 thin films and observation of vortex lattice matching effects

Abstract: Optimized sputtered YBa2Cu3O7 (YBCO) thin films on CeO2-buffered sapphire substrates are patterned into square lattices of submicrometer holes (antidots) with diameters of 250–450 nm and lattice parameters of d=500–1000 nm without deterioration of superconducting properties. In the mixed state, matching effects between the Abrikosov vortex lattice and the artificial antidot lattice are observed. These effects are in the form of peaks or cusps in the critical current density recorded as a function of magnetic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
104
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 18 publications
5
104
2
Order By: Relevance
“…Recent progress in the fabrication of nanostructures provided the possibility to realize superconducting thin films which contain artificial defects as pinning sites with well-defined size, geometry and spatial arrangement. In particular, artificially produced periodic arrays of submicron holes (antidots) [5,6,7,8] and magnetic dots [9,10,11,12] as pinning sites have been intensively investigated during the last years, to address the fundamental question how vortex pinning -and thus the critical current density j c in superconductors -can be drastically increased.In this context, it has been shown that a very stable vortex configuration, and hence an enhancement of the critical current I c occurs when the vortex lattice is commensurate with the underlying periodic pinning array. This situation occurs in particular at the so-called first matching field B 1 = Φ 0 /A, i.e., when the applied field B corresponds to one flux quantum Φ 0 = h/2e per unit-cell area A of the pinning array.…”
mentioning
confidence: 99%
“…Recent progress in the fabrication of nanostructures provided the possibility to realize superconducting thin films which contain artificial defects as pinning sites with well-defined size, geometry and spatial arrangement. In particular, artificially produced periodic arrays of submicron holes (antidots) [5,6,7,8] and magnetic dots [9,10,11,12] as pinning sites have been intensively investigated during the last years, to address the fundamental question how vortex pinning -and thus the critical current density j c in superconductors -can be drastically increased.In this context, it has been shown that a very stable vortex configuration, and hence an enhancement of the critical current I c occurs when the vortex lattice is commensurate with the underlying periodic pinning array. This situation occurs in particular at the so-called first matching field B 1 = Φ 0 /A, i.e., when the applied field B corresponds to one flux quantum Φ 0 = h/2e per unit-cell area A of the pinning array.…”
mentioning
confidence: 99%
“…Kk, 32.80.Pj Introduction -The effects of a periodic array of pinning centers on vortices in superconducting materials have attracted a lot of experimental [1,2,3,4,5] and theoretical [6,7,8,9,10,11,12,13] attention. Of particular interest is the effect of the pinning potential on the melting of a vortex lattice.…”
mentioning
confidence: 99%
“…By using lithography it is possible to create well-defined periodic nanostructured arrays with well-defined periodic pinning structures in which the microscopic pinning parameters, such as size, depth, periodicity, and density, can be carefully controlled. This enhancement of critical currents using periodic arrays has recently been demonstrated for high T c superconductors [1][2][3][4][5][6][7][8][9][10][11]. Therefore, the study of pinning mechanisms and vortex motion, from both the experimental and theoretical point of view, it is important to understand and to create materials with more applicability.…”
Section: Introductionmentioning
confidence: 99%